Analisis Kebutuhan Siswa Melalui AKPD untuk Optimalisasi Layanan Bimbingan dan Konseling di SMK Negeri 7 Medan - Ni Kadek Su Wardani (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2025)
The purpose of this research is to reveal students‘ problems by using AKPD (learner needs questionnaire) at SMK Negeri 7 Medan to find out the main problems that exist in students so that counseling teachers can arrange services according to students’ needs. This research uses descriptive quantitative approach. The research variable is a single variable. The sample involved in this study amounted to 30 students of class XI ULP (Tourism). The sampling technique uses the total population. The data collection technique used the Learner Needs Questionnaire (AKPD). The results showed that the most revealed learner problems were in the personal field as many as 34.22% personal aspects, 28.15% social aspects, 23.41% learning aspects, and 14.22% career aspects.